Directly transferring nanostructural platinum into PtxAy-type nanocompounds for effective catalysis. (February 2023) - Zhang, Chengtian; Liu, Qian; Zhu, Jiawei; Wang, Hong; Mu, Xueqin; Zeng, Weihao; Pu, Zonghua; Wang, Pengyan; Chen, Lei; Yu, Jun; Lin, Rui; Mu, Shichun
Abstract: Although anion-regulated Ptx Ay (A is anion, P, S, Se, Te, etc.) catalysts are promising in energy conversion applications, their facile synthesis is very challenging. Herein, we find a facile and general route to synthesize Ptx Ay -type nanocompounds by anion-regulated-engineering of nanostructural Pt. Taking PtP2 nanocrystals as sample, they can form by one-step phosphorization of Pt nanoparticles dispersed on carbon. PtP2 nanocrystals ∼5 nm in size exhibit excellent hydrogen evolution/oxidation (HER/HOR) and oxygen reduction (ORR) reaction performance. In acidic media, it only requires a HER overpotential of 22 mV to reach the current density of 10 mA cm −2, with exceptional HOR and ORR mass activity, increased by 11.1% and 28.6% compared to Pt catalysts. Also, PtS, PtSe2 and PtTe2 nanocrystals are got by direct sulfuration, selenization, and telluration on nanostructural Pt, respectively, verifying generality of the facile anion-regulation strategy to build Ptx Ay -type nanocompounds and accessibility to industrial-scale synthesis of anion-regulated Pt catalysts. Graphical abstract: Image 1 Highlights: Facile and general synthesis route of Ptx Ay -type nanocompounds is proposed. Ptx Ay (A is anion)-type nanocompounds such as PtP2, PtS, PtSe2 and PtTe2 are built. Pt nanoparticles with rich surface atoms promote synthesis of Ptx Ay -type catalysts. PtP2 /PC exhibits outstanding HER, ORR and HOR electrocatalysis performance. It inspires Ptx Ay -type and other nanocompound synthesis and catalytic applications.